2001
DOI: 10.1139/cjm-47-4-341
|View full text |Cite
|
Sign up to set email alerts
|

Detection of <i>Legionella pneumophila</i> in bioaerosols by polymerase chain reaction

Abstract: Most studies focusing on detecting microorganisms in air by polymerase chain reaction (PCR) have used a liquid impinger to sample bioaerosols, mainly because a liquid sample is easy to be processed by PCR analysis. Nevertheless, the use of multiple-hole impactors for the analysis of bioaerosols by PCR has not been reported despite its great utility in culture analysis. In this study we have modified the impaction onto an agar surface sampling method to impaction onto a liquid medium using the MAS-100 air sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…Legionnaires' disease (LD) is caused mainly by inhalation of aerosols generated from soil or aquatic environments contaminated with Legionella (Pascual et al, 2001). Outbreaks of Legionellosis occur throughout the world affecting public health as well as various industrial, tourist, and social activities (Sabria and Campins, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Legionnaires' disease (LD) is caused mainly by inhalation of aerosols generated from soil or aquatic environments contaminated with Legionella (Pascual et al, 2001). Outbreaks of Legionellosis occur throughout the world affecting public health as well as various industrial, tourist, and social activities (Sabria and Campins, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ] In the study of Pascual et al ., (2001), in a WWTP; three samples from the pretreatment point (30%) and one from the biological treatment (11%) were positive for Legionella . [ 9 ] However, both studies found Legionella in air samples with only PCR, but not with a culture. Although, culture on a selective medium has commonly been used for detection of Legionella spp.…”
Section: Discussionmentioning
confidence: 99%
“…in the wastewater of various units of WWTPs. [ 1 2 3 9 10 ] Therefore, Legionella aerosols can be produced whenever aeration or mechanical agitation is used in wastewater treatment processes. There is evidence that the presence of Legionella in wastewater has been linked with increased levels of antibodies among wastewater irrigation workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Air samples were collected using impact method at two sampling sites, which were selected with respect to the highest expected emissions of the bioaerosol, wind velocity, and direction on the sampling days. To detect the total counts of Enterobacteriaceae bacteria in the air by cultivation method, total number of bacteria by 4′,6-diamidino-2-phenylindole (DAPI) staining, and number of Enterobacteriaceae by in situ hybridization FISH, air samples were collected with the MAS-100 Eco (Merck) using parallel two Petri dishes, each containing 30 ml of phosphate buffered saline (PBS) according to Pascual et al (2001) with own modification. The 4,000 l of air samples was impacted onto the PBS, and afterwards, the PBS was transferred to sterile screw-capped tubes.…”
Section: Methodsmentioning
confidence: 99%